PERAN KONSERVASI LINGKUNGAN SEBAGAI UPAYA MENCAPAI SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Adzkia Husnul Abidat; Nugraheni, Nursiwi (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
To ensure environmental sustainability through conservation practices, global steps are needed. In achieving sustainable development goals, Sustainable Development Goals (SDGs), the role of environmental conservation is important. The research method used in this study is a qualitative approach and analysis of literature from various sources, including research and scientific journals. The findings from this research indicate that the implementation of natural resource and environmental conservation (KSDAL) can make a significant contribution in ensuring the availability of natural resources for future generations. Apart from that, the SDGs program is a joint initiative to preserve the environment, ensuring clean air, safe water, and the opportunity to enjoy the natural beauty of this planet.